The Nova V5584 Sgr: A Short Review - R. Poggiani (Acta Polytechnica CTU Proceedings)
The nova V5584 Sgr was discovered during 2009 October. It has been monitored in different domains of the electromagnetic spectrum: optical, infrared and X-rays. The optical and infrared observations suggest that V5584 Sgr is a Fe II nova that formed dust. No X-ray emission was observed around the time of maximum.